Environmental and structural factors influencing algal communities in small streams and ditches in central Germany. Issue 1 (1st January 2017) - Breuer, Friederike; Janz, Philipp; Farrelly, Eamonn; Ebke, Klaus-Peter
ABSTRACT: The suspended algal fraction in small lotic waterbodies has rarely been investigated as the ecological importance was questioned due to low abundances. Recent findings suggest, that substantial riverine plankton communities can establish in small lotic waterbodies. The gap of knowledge concerning the composition of suspended algal assemblages and influential factors determining their composition is addressed in this study by monitoring suspended and attached algal communities over a two year period in agriculturally influenced small lotic waterbodies using delayed fluorescence spectroscopy. A quantitative comparison of suspended and attached algae indicated, that suspended algae exceeded attached algal biomass in late summer and early autumn. Redundancy analyses and corresponding generalized linear models indicated that the suspended algal groups were most influenced by nutrients, temperature and velocity, whereas light regime was of minor importance. The attached algal groups were affected by the same factors, however with differing intensity. Regional factors, such as season, were identified as the major gradients along which both algal fractions varied, inducing temporal synchronous algal assemblages. This work represents a contribution towards a better understanding of algal ecology specifically suspended algae in small lotic waterbodies.